Comparative Analysis of Zirconium and Lithium Disilicate Restorations in Total Dentures in The Masticatory Areas - Hryn, Vasyl (Global Prosperity, 2025)
The paper examines the current issue of determining the quality of materials for restorations in total dentures in the chewing areas. Restorative dentistry is concerned with the restoration of the shape, function and aesthetics of teeth damaged by caries, trauma or other diseases. Restoration of chewing teeth ensures the restoration of chewing function, prevents rapid wear of the prosthesis and reduces the load on the remaining teeth and jaw structures. Improving aesthetics is of great importance. Restoration of the color, shape and length of the teeth helps to improve the appearance and increase patient satisfaction. The growing demand for durable and aesthetic dental restorations, especially in total prostheses, highlights the key role of modern ceramic materials. Zirconium dioxide (ZrO2) and lithium disilicate (Li2Si2O5) are the leading options due to their mechanical and optical properties. Despite their widespread use, data on their long-term clinical effectiveness and patient satisfaction in full dentures in the chewing areas are limited. This study aims to comparatively evaluate the properties, aesthetics, durability, and patient satisfaction with these restorations, focusing on the chewing segments. Analysis of available scientific studies and clinical reviews shows that zirconium dioxide demonstrates higher strength and fracture resistance, making it suitable for posterior restorations, with excellent survival rates for monolithic forms. At the same time, lithium disilicate (360 MPa) provides better optical characteristics and significantly higher patient aesthetic satisfaction (p < 0.05). The choice of material for full dentures in chewing areas requires a balance between mechanical requirements and aesthetic priorities. Zirconium dioxide is best for loaded areas, while lithium disilicate is chosen when transparency and natural appearance are important. Zirconium and lithium disilicate demonstrate high clinical efficacy, but have different advantages depending on the conditions of use. Zirconium is characterized by the highest mechanical resistance and a lower incidence of chipping, making it optimal for chewing areas. Lithium disilicate, on the other hand, provides better aesthetic characteristics and has a slightly higher survival rate in anterior restorations. The rational choice of material should be based on the clinical situation, the location of the restoration, and the individual needs of the patient.